2022
DOI: 10.1111/ggi.14427
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance phase angle and sarcopenia in older patients with prostate cancer

Abstract: Aim The purpose of this study was to evaluate the factors associated with the bioimpedance phase angle (PhA) in older patients with prostate cancer, and to determine the optimal cutoff for the PhA in patients with sarcopenia and prostate cancer. Methods This retrospective cross‐sectional analysis enrolled patients with prostate cancer aged ≥60 years. Appendicular skeletal muscle mass and PhA estimated by bioimpedance analysis, grip strength, the five‐time chair stand test, gait speed, the Short Physical Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…Based on the results above ( Table 1 ), we find that, in terms of cancer, low PhA is associated with sarcopenia risk in patients, particularly in gastric cancer ( 25 ), colorectal cancer ( 24 ), and prostate cancer ( 26 ). However, PhA has only been proven to be associated with malnutrition rather than sarcopenia in some types of cancers ( 29 34 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Based on the results above ( Table 1 ), we find that, in terms of cancer, low PhA is associated with sarcopenia risk in patients, particularly in gastric cancer ( 25 ), colorectal cancer ( 24 ), and prostate cancer ( 26 ). However, PhA has only been proven to be associated with malnutrition rather than sarcopenia in some types of cancers ( 29 34 ).…”
Section: Discussionmentioning
confidence: 82%
“…Following extensive studies that compared patients with cancer to those without it, the former have been found to have a higher risk of developing cachexia, which can easily result in malnutrition and muscle loss, and lead to sarcopenia ( 6 , 23 ). Based on the EWGSOP diagnosis criteria for sarcopenia, many studies have proved that a low PhA predicts sarcopenia risk in patients with colorectal cancer ( 24 ), gastric cancer ( 25 ), and prostate cancer ( 26 ). A cross-sectional study conducted with 124 patients in total with solid or hematologic cancer found that a low PhA is highly correlated with a high risk of sarcopenia [odds ratio (OR) = 1.74; 95% confidence interval (CI), 1.03–2.93; P < 0.035], after adjusting for hydration ( 27 ).…”
Section: Pha Prediction For Sarcopenia In Patients With Cancermentioning
confidence: 99%
“…The BIA-derived PhA holds promise in clinical settings due to its ease of measurement and reliable representation of nutritional status and muscle mass in sarcopenic and cancer patients [ 12 , 16 , 24 , 25 ]. Therefore, we investigated the value of BIA-derived PhA in non-sarcopenic RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The BIA-derived phase angle (PhA) reflects cellular health and is correlated with the prognosis of various diseases [ 9 , 10 , 11 ]. Recent studies have emphasized its potential for diagnosing sarcopenia [ 12 ]. A low PhA is associated with diminished muscle strength [ 13 ], and is prevalent in sarcopenic patients [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation